2004
DOI: 10.1161/01.cir.0000109140.51366.72
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Is Involved in Outward Arterial Remodeling

Abstract: Background-Toll-like receptor 4 (Tlr4) is the receptor for exogenous lipopolysaccharides (LPS). Expression of endogenous Tlr4 ligands, heat shock protein 60 (Hsp60) and extra domain A of fibronectin, has been observed in arthritic and oncological specimens in which matrix turnover is an important feature. In atherosclerosis, outward remodeling is characterized by matrix turnover and a structural change in arterial circumference and is associated with a vulnerable plaque phenotype. Since Tlr4 ligands are expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(133 citation statements)
references
References 38 publications
6
124
0
3
Order By: Relevance
“…The first evidence derives from data on the cellular expression and involvement of the TLR-4 signaling pathway in atherosclerotic arteries, and precisely on ECs, macrophages [108,109] and adventitial fibroblasts of these arteries [110]. In 2004, the group of De Kleijn [111], using a femoral artery cuff model in the atherosclerotic ApoE3 (Leiden) transgenic mouse and inducing plaque formation through LPS-mediated TLR-4 activation, demonstrated that the TLR-4 signaling pathway is involved in outward arterial remodeling, probably through up-regulation of TLR-4 itself and its ligands. In 2006, Lin and colleagues [112], by using cell cultures of human aortic smooth muscle cells (HASMCs) from vessels obtained from Zeal and white rabbits treated or without intravenous injections of LPS (110 ng/kg), evidenced that the stimulation of HASMCs with LPS significantly increased the TLR-4 expression.…”
Section: Role Of Tlr-4 Pathway In Aneurysms (Sporadic Taa)?mentioning
confidence: 99%
“…The first evidence derives from data on the cellular expression and involvement of the TLR-4 signaling pathway in atherosclerotic arteries, and precisely on ECs, macrophages [108,109] and adventitial fibroblasts of these arteries [110]. In 2004, the group of De Kleijn [111], using a femoral artery cuff model in the atherosclerotic ApoE3 (Leiden) transgenic mouse and inducing plaque formation through LPS-mediated TLR-4 activation, demonstrated that the TLR-4 signaling pathway is involved in outward arterial remodeling, probably through up-regulation of TLR-4 itself and its ligands. In 2006, Lin and colleagues [112], by using cell cultures of human aortic smooth muscle cells (HASMCs) from vessels obtained from Zeal and white rabbits treated or without intravenous injections of LPS (110 ng/kg), evidenced that the stimulation of HASMCs with LPS significantly increased the TLR-4 expression.…”
Section: Role Of Tlr-4 Pathway In Aneurysms (Sporadic Taa)?mentioning
confidence: 99%
“…Evidence that EDA may act as a trigger for atherogenesis is accumulating. EDA levels are elevated in plasma of ApoE knockout mice [23] and EDA mRNA levels are increased during Tlr4-dependent outward remodeling [18]. Furthermore, in atherosclerotic mice lacking EDA, atherosclerotic lesion areas were found to be reduced in number and size [23].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we and others showed that Tlr4 activation accelerates arterial occlusion by neointima formation, plaque formation, geometrical remodeling and plaque destabilization [18][19][20][21]. It remains unclear which ligands activate Tlr4 and thereby promote atherosclerotic luminal narrowing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, enhanced expression of hTLR4 was associated with elevations of IL-1β and TNF-α. Evidence is accumulating that outward arterial remodeling is associated with vulnerable plaque phenotype [19] and increase in hTLR4 expression [20]. Ameziane et al [21] showed that polymorphism of Gly299 allele of the hTLR4 gene is associated with reduction in acute coronary events.…”
Section: Discussionmentioning
confidence: 99%